Misperceiving Economic Success: Experimental Evidence on Meritocratic Beliefs and Inequality Acceptance - Dietmar Fehr; Martin Vollmann (Center for Economic Studies and ifo Institute (CESifo), 2022)
Meritocratic beliefs are often invoked as justification of inequality. We provide evidence on how meritocratic beliefs are shaped by economic status and how they contribute to the moral justification of inequality. In a large-scale survey experiment in the US, we show that success causes a change in beliefs about success depending on effort rather than luck. Exploiting exogenous variation in meritocratic beliefs in a two-stage analysis shows that beliefs affect how much inequality people accept. Successful people prefer to remain ignorant about the true underlying reasons for success and there is no evidence that beliefs are moderated by political orientation.
Keywords: D31; D63; C93; H23; H24; 330; meritocratic beliefs; inequality acceptance; fairness; political views; survey experiment